An RNAi screen of RNA helicases identifies eIF4A3 as a regulator of embryonic stem cell identity. Issue 21 (23rd November 2022) - Li, Dan; Yang, Jihong; Malik, Vikas; Huang, Yuting; Huang, Xin; Zhou, Hongwei; Wang, Jianlong
Abstract: RNA helicases are involved in multiple steps of RNA metabolism to direct their roles in gene expression, yet their functions in pluripotency control remain largely unexplored. Starting from an RNA interference (RNAi) screen of RNA helicases, we identified that eIF4A3, a DEAD-box (Ddx) helicase component of the exon junction complex (EJC), is essential for the maintenance of embryonic stem cells (ESCs). Mechanistically, we show that eIF4A3 post-transcriptionally controls the pluripotency-related cell cycle regulators and that its depletion causes the loss of pluripotency via cell cycle dysregulation. Specifically, eIF4A3 is required for the efficient nuclear export of Ccnb1 mRNA, which encodes Cyclin B1, a key component of the pluripotency-promoting pathway during the cell cycle progression of ESCs. Our results reveal a previously unappreciated role for eIF4A3 and its associated EJC in maintaining stem cell pluripotency through post-transcriptional control of the cell cycle.